Charles V and the University of Granada, a new historical-artistic itinerary - Tejero López, Miriam (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Carlos V founded the University of Granada in 1526. The permanence o the founding memory in the city of Granada is manifested by an important and numerous artistic heritage that evokes and links it to its historical past. The aim is to convert the university heritage into cultural product, through the creation of a historical-artistic itinerary, which delves into the facet of the emperor as an educational patron, and which allows overcoming the reduced concept of the university as a temple of knowledge.